2017
DOI: 10.1055/s-0043-119219
|View full text |Cite
|
Sign up to set email alerts
|

Technical aspects of endoscopic ultrasound (EUS)-guided sampling in gastroenterology: European Society of Gastrointestinal Endoscopy (ESGE) Technical Guideline – March 2017

Abstract: This Guideline from the European Society of Gastrointestinal Endoscopy (ESGE) focuses on technical aspects of endoscopic ultrasonography (EUS)-guided sampling in gastroenterologythe choice of needle, sampling technique, and specimen handling and processing -and updates the previous guideline on these topics published in 2012 [1]. The target audience for this Guideline is endoscopists who perform EUS-guided sampling. Indications, results, and clinical impact of EUS-guided sampling are addressed in a separate cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
314
2
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 303 publications
(354 citation statements)
references
References 136 publications
(230 reference statements)
6
314
2
12
Order By: Relevance
“…Endoscopic ultrasound (EUS)‐guided sampling is an established method of obtaining specimens for the pathological diagnosis of solid masses, including pancreatic tumors, subepithelial tumors (SET), and lymph node lesions . Two types of needles are used for EUS‐guided sampling with fine‐needle biopsy (FNB) and fine‐needle aspiration (FNA) needles .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic ultrasound (EUS)‐guided sampling is an established method of obtaining specimens for the pathological diagnosis of solid masses, including pancreatic tumors, subepithelial tumors (SET), and lymph node lesions . Two types of needles are used for EUS‐guided sampling with fine‐needle biopsy (FNB) and fine‐needle aspiration (FNA) needles .…”
Section: Introductionmentioning
confidence: 99%
“…Endoscopic ultrasound (EUS)‐guided sampling is an established method of obtaining specimens for the pathological diagnosis of solid masses, including pancreatic tumors, subepithelial tumors (SET), and lymph node lesions . Two types of needles are used for EUS‐guided sampling with fine‐needle biopsy (FNB) and fine‐needle aspiration (FNA) needles . FNB needles are designed to procure samples in a way that preserves the tissue architecture for histological evaluations; they feature either a particular cutting‐tip geometry or a beveled side hole in the distal portion of the needle .…”
Section: Introductionmentioning
confidence: 99%
“…The fanning technique allows for targeting multiple areas within the mass during each needle pass and hence reduces the chance of sampling error. Also, the technique is not associated with an additional risk or cost . However, the evidence is limited to one study in patients with pancreatic masses that showed advantages of fanning in terms of sample adequacy but failed to show a significant impact on diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the technique is not associated with an additional risk or cost . However, the evidence is limited to one study in patients with pancreatic masses that showed advantages of fanning in terms of sample adequacy but failed to show a significant impact on diagnostic accuracy. Finally, during back‐and‐forth thrusting movements, there could be a possibility of missing out visualization of the needle on new horizontal plane according to torqueing the scope body for targeting different area within the mass.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation